P0906SALUBRINAL IMPROVES OSTEOCLAST DIFFERENTIATION AND VASCULAR CALCIFICATION IN UREMIC MILLENNIUM THROUGH INHIBITION OF THE ENDOPLASMIC RETICULUM (ER) STRESS CONDITION. (6th June 2020) - Zheng, Cai-Mei; Chiu, Hui-Wen; Lu, Kuo-Cheng; Lu, Chien-Lin; Wu, Mai-Szu; Hsu, Yung-Ho
Abstract: Background and Aims: Chronic kidney disease (CKD) is a globally increasing health problem especially in aged era. CKD-mineral and bone disorder (CKD-MBD) becomes a principal consequence of CKD, which includes mineral abnormalities, vascular calcifications (VC) and renal osteodystrophy (ROD), and patients eventually present with fractures and cardiovascular disease (CVD) (Figure 1). Thus, bone loss in CKD patients relates closely with cardiovascular calcification. The endoplasmic reticulum (ER) stress is triggered by many clinical conditions unique to CKD, including uremic toxins, chronic inflammation, metabolic acidosis, proteinuria, malnutrition, etc. In our study, we hope to evaluate the ER stress inhibitor, salubrinal as targeted therapy for CKD related bone loss and vascular calcification. Methods: Isolation of primary osteoclasts from long bone primary cell culture: Femoral and tibia bone from 8-week-old Sprague–Dawley rats were removed and used as primary osteoclast cultures. Osteoclast precursor cells were seeded in 96-well plates (2.0 x 104 cells/well) and cultured for 6 days in alpha minimum essential medium (α-MEM) supplemented with 10% FBS, 50 ng/ml M-CSF and 50 ng/ml RANKL in the absence or presence of uremic toxins. The whole process of osteoclast development in cell cultures was divided into first M-CSF–dependent growth of osteoclast progenitor's phase and latter phase is RANKL induced terminal differentiation phase. The experiment is performed with the approval of the Laboratory Animal Center of the Taipei Medical University in Taipei, Taiwan. Primary Human Aorta Vascular Smooth Muscle Cell Culture: Primary human aorta vascular smooth muscle cells (VSMC) were isolated by ScienCell Research Laboratories, Inc. (Carlsbad, CA) and purchased through Innoprot (Derio, Spain). We examined the role of uremic toxin on ER stress and autophagy using osteoclasts and vascular smooth muscle cells cultured with uremic toxins including PTH, p-cresylsulfate (pCS) and p-cresylglucuronide (pCG), indoxyl sulfate, asymmetric dimethylarginine (ADMA), and homocysteine. The cells are treated with salubrinal with or without toxins and see how ER stress and autophagy effects on survival and differentiation of osteoclasts and VSMC cells. Results: We found that ER stress and autophagy related mRNA were increased in osteoclasts using GEO database analysis, revealed that ER stress and autophagy play an important role in osteoclast differentiation. Further, we revealed that uremic toxins increased the autophagy and ER stress status and increased the osteoclasts differentiation. Treatment of the osteoclasts under uremic millennium with salubrinal, an ER stress inhibitor, inhibited the ER stress and osteoclast differentiation. Uremic toxins also increased the ER stress in human vascular smooth muscle cells (VSMCs). After treated with salubrinal, the calcification and proliferation improved in these cells. Conclusion: ER stress increases osteoclast differentiation and vascular calcification in uremic millennium, and salubrinal improves these conditions through inhibition of ER stress. Thus, salubrinal probably might be used as targeted therapy for vascular calcification and bone loss in CKD patients.